Effect of exogenous Phytase on Egg Production and Egg Quality of Spent Hen - Bashar, MK; Howlider, MAR; Bulbul, SM (Bangladesh Journal of Livestock Research, 2020)
The present study determined, assessed and quantified the exogenous phytase on egg production and egg quality of spent hens. Ninety laying hens (ISA- Brown) received iso-energetic and iso-nitrogenous diet supplemented with 0, 0.05, 0.1, 0.15 and 0.2 % phytase and reared in cages. Each layer was fed 120g feed/day from 90 to 100 weeks of age. At the inception of the study the spent hen at the age of 90 weeks had an average egg production 65.21 %. Phytase addition in diet increased (p<0.05) egg production (7.67, 12.17, 12.04 and 15.87 % higher than control group), egg mass output (5.5, 9.34, 7.65 and 12.72 % higher than that of control) and feed conversion, but it did not alter shell weight, shell thickness, shape index, albumen index, Haugh unit, per cent yolk and yolk color. It was concluded that reduced egg production of spent hen at older ages to some extent might have a relationship to decreased availability of phosphorus. The decreased egg production in hens at older ages could be corrected by adding appropriate phytase level in the diet. Thus, it may be possible to extend and prolonged productive life of spent hens by supplying exogenous phytase in diet. However, the effect of availability of phosphorus on egg production using larger population for a longer period may be performed to confirm the findings of the current study. Bangladesh J. of Livestock Res. 20(1-2): 68-76, Jan-Dec 2013